Determinants of supermarket entry in Mexico - Castañeda, Alejandro; Ibarra, Pedro (Estudios Económicos de El Colegio de México, 2019)
We estimate reduced form models, the profits are function of observable variables, to analyze the determinants of supermarket entry. We find that more concentrated markets, constructed on chain information, diminish the incentives to enter a market. Additionally, by controlling for market concentration and by analyzing the specific impact of brand chain, we find that a larger number of Walmart stores increase the feasibility of zero and one store in the relevant market and diminishes the feasibility of two or more stores in the market. For the other chains we find an opposite result.